Geophysical Subsurface Gravity Survey Modeling Of Segamat- Kuantan Using Matlab - Khazali, Mohamad Razif (Universiti Sains Malaysia, 2018)
In this project, geophysical methods of gravity survey are conducted in order to study subsurface geology profile along Tun Abdul Razak (Segamat-Kuantan) Highway. The area of study is generally located in the southeastern Pahang region and the northern Segamat region. Generally, the lithology structure for this area consists of sedimentary, basalt, meta-sediment and quaternary unconsolidated deposit which refers to loose materials. Gravity data profile for each station is less accurate due to the vibration and noise caused by the traffic on a highway. A barometric method used to calculate the elevation base on pressure differential and the data received is not accurate cause by the temperature at surrounding. A gravity survey was carried out using Gravimeter to measure a change in gravity acceleration due to the gravitational acceleration on subsurface materials. Furthermore, the gravity data for this project influenced by the density of underlying rock subsurface and topography of this area. The density of rock along this survey area was recorded to obtain density data and requirement for 2-dimension modeling. The range of observed gravity between 0.89 to 6.62 milligal toward Kuantan. The highest observed gravity is 6.62 milligal at station number two. The reading may be affected by the density subsurface geology range between 2.9 (